Knowledge of diverse learners : implications for the practice of teaching. - Abd Rahman, Fadzilah (International Journal of Instruction, 2010)
Knowledge of Diverse Learners (KDL) is increasingly recognized as an essential component of knowledge base for effective teaching as in today’s schools, teachers must be prepared to teach a diverse population of student (Banks et al. 2005). In other words, teachers need to be aware that their students in a classroom are and always have been different from one another in a variety of ways. KDL refers to an understanding of diversity of students in terms of their abilities and interests and how they respond to diverse situations; an application of different teaching strategies; and how various types of classroom activities might be managed. Although KDL has come to be seen as important, details of its development, depth and quality among pre-service teachers (PSTs) has remained something of mystery, as has the capability of PSTs to adapt and employ KDL into their actual teaching. As an effort to develop coherent understanding of the feature of prospective teachers regarding KDL, this paper addresses three questions. First, to what extent are the PSTs prepared for KDL as they are finishing the teacher education programmes? Secondly, how do the PSTs apply the KDL in their teaching practices? Thirdly, how do PSTs reflect on their practice in undertaking the elements of KDL during the teaching practices? This paper illustrates the results of a study involving a sample of 74 PSTs at a university in Malaysia. At the beginning of the study, 74 PSTs were given a questionnaire. 11 PSTs have been observed and interviewed. Result indicates that PSTs were able to develop KDL and show their understanding of it, yet not readily apply such knowledge in modified situations.